(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
Brown tumor is a benign bone lesion that arises as a direct result of parathyroid hormone on bony tissue in some patients with hyperparathyroidism. Multiple brown tumors may simulate malignant disease and it is a real challenge for the clinicians in the differential diagnoses. Brown tumor as the only and initial symptom of normocalcemic primary hyperparathyroidism is a rare clinical entity. Here, we present a case with multiple brown tumors in a young normocalcemic woman as a sequele of primary hyperparathyroidism mimicking bone metastases. Bangladesh J. Nuclear Med. 22(1): 68-72, Jan 2019